Analysis and modeling techniques for ultrasonic tissue characterization - Maggio, Simona <1984> (Alma Mater Studiorum - Università di Bologna, 2011)
This thesis introduces new processing techniques for computer-aided interpretation of ultrasound images with the purpose of supporting medical diagnostic. In terms of practical application, the goal of this work is the improvement of current prostate biopsy protocols by providing physicians with a visual map overlaid over ultrasound images marking regions potentially affected by disease. As far as analysis techniques are concerned, the main contributions of this work to the state-of-the-art is the introduction of deconvolution as a pre-processing step in the standard ultrasonic tissue characterization procedure to improve the diagnostic significance of ultrasonic features. This thesis also includes some innovations in ultrasound modeling, in particular the employment of a continuous-time autoregressive moving-average (CARMA) model for ultrasound signals, a new maximum-likelihood CARMA estimator based on exponential splines and the definition of CARMA parameters as new ultrasonic features able to capture scatterers concentration. Finally, concerning the clinical usefulness of the developed techniques, the main contribution of this research is showing, through a study based on medical ground truth, that a reduction in the number of sampled cores in standard prostate biopsy is possible, preserving the same diagnostic power of the current clinical protocol. === Cette thèse introduit de nouvelles techniques de traitement pour l’interprétation guidée d’images ultrasons, dans le but de soutenir le diagnostic médical. L’objectif pratique de ce travail est l’amélioration du protocole standard pour la biopsie de la prostate, en fournissant au médecin une carte visuelle sur l’écographie qui marque les régions potentiellement malignes. En ce qui concerne les techniques d’analyse, la contribution principale de cette thèse est l’introduction de la déconvolution comme étape de pré-traitement dans la procédure standard de caractérisation des tissus par ultrasons, afin d’améliorer la valeur diagnostique des caractéristiques du signal. Cette thèse présente, en outre, des innovations dans la modélisation du signal ultrason, en particulier la proposition d’un modèle autorégressif à moyenne glissante en temps continu (CARMA), le développement d’un nouvel estimateur au maximum de vraisemblance de paramètres CARMA fondé sur les splines exponentielles et la définition des paramètres CARMA comme des nouvelles caractéristiques du signal ultrason capables de capturer l’information sur la concentration de scatterers. Enfin, concernant l’utilité clinique des techniques développées, la contribution principale de cette recherche est dans la démonstration, au travers d’une étude médicale, de la possibilité de réduire concrètement le nombre d'échantillons prélevés pendant la biopsie de la prostate standard, en préservant le même pouvoir diagnostique du protocole biopsique standard.